If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -3) = -2(x + -7) Reorder the terms: 6(-3 + x) = -2(x + -7) (-3 * 6 + x * 6) = -2(x + -7) (-18 + 6x) = -2(x + -7) Reorder the terms: -18 + 6x = -2(-7 + x) -18 + 6x = (-7 * -2 + x * -2) -18 + 6x = (14 + -2x) Solving -18 + 6x = 14 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -18 + 6x + 2x = 14 + -2x + 2x Combine like terms: 6x + 2x = 8x -18 + 8x = 14 + -2x + 2x Combine like terms: -2x + 2x = 0 -18 + 8x = 14 + 0 -18 + 8x = 14 Add '18' to each side of the equation. -18 + 18 + 8x = 14 + 18 Combine like terms: -18 + 18 = 0 0 + 8x = 14 + 18 8x = 14 + 18 Combine like terms: 14 + 18 = 32 8x = 32 Divide each side by '8'. x = 4 Simplifying x = 4
| 6x+18=10x-6 | | 47=5x-(7-4x) | | 7x+3y=50000 | | -(3x+5)=2x | | -d+4e=-3 | | -6(x-6)=3(0+x) | | 0.5=0.4 | | R+2-3=4 | | x+(x-20)=78 | | 11x-7(-4+2x)=-14 | | 7x+3=56 | | -4x^2-5.5x+5=0 | | -5x-4(-3x+15)=3 | | -6(-v-3y+4)= | | 2x^2-4x+4=25 | | 0.8x-4=1.5x+0.2 | | 48.15/45 | | 0.8x-4=1.5+0.2 | | f(x)=x^4+8x^2-12 | | x^2-2x=10.5 | | 3x+4(-4x+16)=8 | | 3x+10=2x+x+18 | | 4+33x=95 | | xsquared-2x=10.5 | | -2x+4x=56 | | -29+(-25)= | | 3(2u+7)=-12+8u | | 85/5= | | 7(2x-5)=4(6x-2)+x | | 2/3m-10=-12 | | 3x^2+81x-972=0 | | 10x+30=10x+60 |